Strategi Pemasaran Menggunakan Analisis SWOT Untuk Meningkatkan Kunjungan Pasien Pada Klinik Griye Sehat Di Cilegon - M Yusron; Ade Norma; Endang Dwi Amperawati (Prosiding Amal Insani Foundation, 2023)
This study focuses on exploring and analyzing various variables that constitute the strengths, weaknesses, opportunities, and threats of Griye Sehat Cilegon Clinic. The study also aims to identify and evaluate the clinic's marketing strategies to increase patient visits and address various problems associated with marketing strategy implementation. Using a qualitative approach, this research was conducted through a descriptive method, where data was obtained through in-depth interviews with the clinic's owner, employees, and consumers. SWOT analysis was used as the primary analytical tool, while the 4P marketing framework (Product, Price, Promotion, Place) was utilized as the basic framework for interview questions. The research findings indicate that Griye Sehat Cilegon Clinic is positioned in Quadrant I of the SWOT analysis, with an internal strength score of 3.36, weakness score of 3.08, opportunity score of 3.49, and threat score of 3.33. This suggests that the clinic is in a favorable position where its opportunities and strengths can be utilized to overcome threats. Based on these findings, it is recommended for the clinic to implement an aggressive growth-oriented strategy to maximize its potential and capitalize on the available opportunities.